OPTIMISASI PENYUSUNAN JADWAL MATA KULIAH DENGAN PROGRAM GOL - Samuel Jun Harli; Endang Lily; M. D. H. Gamal (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
This paper discusses a mathematical modeling to establish a course schedule opti-mally. Goal programming model formed is utilized to maximize the satisfaction of the desired values while still meeting the specied limits: limits on days, the time span, the number of faculties, the number of rooms allocated, the number of stu-dents taking the courses, the number and type of courses that will be scheduled.